Strategi Pengajaran Islami Guru PAI di Sekolah Dasar Muhammadiyah Boarding Shocool (MBS) Ummat - Wati, Salma; Fitriani, Fitriani; Lisa, Miratun; Ulyana, Lili; Sudirman, Sudirman; Ida Astini, Baiq (Diksi: Jurnal Pendidikan dan Literasi, 2025)
The purpose of writing this article is to describe the teaching strategies for Islamic religious education as well as their effectiveness on the moral and spiritual development of students. This study employs a qualitative approach, utilising a case study method that involves observation, interviews, and documentation as data collection techniques. The results of the study show that PAI teachers at MBS Ummat implement teaching strategies based on Islamic principles, such as exemplary (uswatun hasanah), advice (mau'izah), and habituation of worship. This strategy is supported by the use of interactive and varied learning media, as well as approaches that are contextual and relevant to students' daily lives. Additionally, the support of the Islamic school environment plays a crucial role in the success of this strategy. This study concludes that the Islamic teaching strategies applied in MBS Ummat are effective in increasing religious understanding and the formation of Islamic character in students. Recommendations are given for continuous improvement in teacher professional development and the use of technology in teaching.